Kearifan Lokal Masyarakat Suku Bajo Studi Etnografi Nilai-Nilai Pendidikan Agama Islam dan Budi Pekerti Pada Praktek Ritual Keagamaan Di Desa Bajo Kecamatan Tilamuta - Dai, Fadhliyah; Manahung, Ramoend (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2020)
Abstract The purpose of the research to know the general sense of wisdom sentence, the definition of local wisdom and the value of Islamic education in local wisdom in the village of Baco, District Tialmuta. This type of research is qualitative research. The approach to cultural studies of the theory used is theoretical ipsichoorial, structuration, hegemony, social practice and semiotics. Data collection techniques include participatory observation, in-depth interviews, literature studies and focused group discussions. The Data in the sports are descriptitically and presented in narrative form, table, and danilustrasifisual. The results showed that: 1) in general, this sentence of wisdom, interpreted as an invitation so that we can see the purpose of our lives, in a way that we are healthy to always manage the resources that we have at the optimum, not only Optimum, not only availability, but also sustainability to be available, can create the ability for us to see our needs properly and fulfill them, willing to always consistently travel towards that goal. 2) The local wisdom is the values that apply in a society. The values are believed to be the truth and become a reference in the daily conduct of local communities. Therefore, it is very reasonable to say that the local wisdom is the entity that determines the human dignity and dignity of the community. 3) to teach us that man and nature is a supreme harmony of the works of God Almighty. The human being as a symbol of sustainability and harmony of natural life as a living place is always filled with a smile Keywords: local wisdom, Islamic religious education value, Bajo village